1982
DOI: 10.1139/y82-222
|View full text |Cite
|
Sign up to set email alerts
|

Plasma parathyroid hormone and divalent cation response to induction of acute metabolic acidosis

Abstract: Since the effect of acute administration of acid upon blood magnesium and parathyroid hormone (PTH) is unclear we infused anesthetized dogs with saline (controls), HCl, lactic, and methylmalonic acids for 3 h. In all groups but lactic acid, plasma magnesium decreased; ionized calcium levels were increased by all three acids. Nevertheless, PTH increased in each of six dogs following methylmalonic acid and decreased in four of six animals after lactic acid. The decrease in plasma magnesium concentration after me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 2 publications
3
6
0
Order By: Relevance
“…We showed that the acute induction of both Met Acid and Resp Acid stimulated PTH secretion. Although our results in acute Met Acid are similar to those in previous studies, those studies did not control for acidosis‐induced changes in the plasma calcium concentration (1,2,5) . In a study that reversed the sequence and corrected Met Acid while controlling for changes in ionized calcium, the rapid correction of Met Acid reduced PTH values (31) .…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…We showed that the acute induction of both Met Acid and Resp Acid stimulated PTH secretion. Although our results in acute Met Acid are similar to those in previous studies, those studies did not control for acidosis‐induced changes in the plasma calcium concentration (1,2,5) . In a study that reversed the sequence and corrected Met Acid while controlling for changes in ionized calcium, the rapid correction of Met Acid reduced PTH values (31) .…”
Section: Discussionsupporting
confidence: 73%
“…A confounding factor is that these studies did not control for acidosis‐induced increases in the ionized calcium concentration. In previous studies of acute Met Acid and Resp Acid, it has been reported that (1) Met Acid increases PTH levels although ionized calcium values increase (2,5) and (2) Resp Acid does not affect PTH levels. But this latter observation was in a setting in which the effect of an increased ionized calcium value was not determined (6) …”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Acidosis can also increase serum PTH concentration, but results are quite conflicting (Oster et al 1982).…”
Section: Discussionmentioning
confidence: 99%